Yoruba Dundun Sekere Traditional Music in the Palace of the Alaafin of Oyo - Ajewole, John; Bello, Abayomi (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024, 2024)
This study focuses on the Yoruba traditional Dundun-Sekere music in the palace of the Alaafin of Oyo. It traces and explores the Yoruba traditional music and Dundun- Sekere ensemble; the study also examines the Dundun -Sekere ensemble of the Alaafin of Oyo; and discusses the textual analysis of the Dundun-Sekere music. This study relied solely on oral tradition, written documents, and live musical performance approaches. The research combines historiographical and ethnomusicological approaches. Historical oral information was collected through interviews with twenty (20) Yoruba traditional court musicians found in the palace of the Alaafin of Oyo who specialize in the performance of different types of traditional music in general and the Dundun-Sekere musicians in particular. The results show that Yoruba traditional music is entirely different from that of Western Europe. The music of the Yoruba society reveals a great deal about its beliefs and sentiments. Music has always been used in the Yoruba traditional cultures to celebrate various ceremonies.  Musicianship in the Yoruba traditional society is hereditary. One thing about the Dundun-Sekere ensemble is that the musicians play their instruments and sing along at the same time. The Dundun-Sekere music originated from the Alaafin’s court before it spread to other parts of Yoruba land. In conclusion, the Oyo Alaafin’s court is the home of the Dundun-Sekere music. The Dundun-Sekere musicians in Oyo have experienced professionals. It should be noted that it is only the Sekere of the Alaafin of Oyo that has cowries and shells in Yoruba land. Others have beads. It is suggested that the music – of the Dundun Sekere ensemble should be documented, recontextualized, and repackaged to teach the upcoming generation and the Yoruba in the diasporas. Keywords: Yoruba, Traditional, Court Music, Alaafin, and the Palace